Molecular phylogenetics of Chelonopsis (Lamiaceae: Gomphostemmateae) as inferred from nuclear and plastid DNA and morphology. Issue 2 (27th December 2018) - Xiang, Chun-Lei; Zhang, Qiang; Scheen, Anne-Cathrine; Cantino, Philip D.; Funamoto, Tsuneo; Peng, Hua
Abstract: The recently established tribe Gomphostemmateae (Lamiaceae) consists of Gomphostemma, Bostrychanthera and Chelonopsis, but relationships within and between these genera have not been well studied. Only six of the approximately 46 species of Gomphostemmateae have been included in any previous phylogenetic analysis. In the present study, we used DNA sequences of two nuclear regions (ITS, ETS) and five plastid loci ( psbA–trnH, rps16, trnL intron, trnL–trnF spacer, trnS–trnG ) to reconstruct the phylogeny of the East Asian genus Chelonopsis for the first time. The molecular results indicate that the tribe Gomphostemmateae is monophyletic; Bostrychanthera is embedded in Chelonopsis ; and Chelonopsis comprises two clades, one encompassing the taxa of Chelonopsis subg. Chelonopsis and the genus Bostrychanthera and the other consisting of Chelonopsis subg. Aequidens . This split is supported by several morphological characters. These results, which are further strengthened by morphological and cytological data, indicate that Bostrychanthera should be transferred to Chelonopsis . In addition, our results show that within C. subg. Aequidens, sect. Aequidens and sect. Microphyllum are monophyletic. Furthermore, two major clades are concordant with the Sino–Japanese and Sino–Himalayan distribution patterns.